ANALYSIS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN PERSONALIZING EDUCATION MARKETING - Haniatin, Maimanatin Haniatin; Wijaya, Andi; Himmah, Hanim Faiqotul; Rizal, Fathur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the use of Artificial Intelligence (AI) in personalizing educational marketing, with a focus on improving user experience and operational efficiency of educational institutions. The background to this research is driven by the rapid development of digital technology which encourages educational institutions to adapt to more personalized and data-based marketing strategies to increase competitiveness in an increasingly competitive market. The research method used is a qualitative method with a case study approach and in-depth interviews with related parties, such as public relations, school principals and students. The research findings show that the application of AI in educational marketing can increase advertising personalization, speed up the decision-making process for prospective students, and optimize marketing operational processes. Additionally, the use of machine learning and big data analysis allows educational institutions to target more relevant audiences and increase enrollment conversion rates. The contribution of this research is to provide insight into how AI can be used as a strategic tool in increasing the effectiveness of educational marketing, as well as suggesting a wiser application of technology to achieve optimal results in the context of educational marketing in the digital era.